2016
DOI: 10.1002/cphc.201500953
|View full text |Cite
|
Sign up to set email alerts
|

Red‐Tuned Mn d–d Emission in Doped Semiconductor Nanocrystals

Abstract: Light-emitting Mn-doped semiconductor nanocrystals have been extensively studied for the last three decades for their intense and stable Mn d-d emission. In principle, this emission should be fixed at 585 nm (yellow), but recent studies have shown that the emission can be widely tuned even to 650 nm (red). This is a spectacular achievement as this would make Mn-doped nanocrystals efficient and tunable light emitters. Keeping these developments in view, the chemistry of the synthesis of these materials, their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 67 publications
5
67
1
1
Order By: Relevance
“…However, as shown in Figure 1, Mn doped in NCs do not present around 585 nm emission but a red-shift, and the PL shifts more towards the red region with the increase of Mn levels in Mn:AIZ/ZnS NCs. The red-shift by Mn doping was also observed in AIZS and other host NCs [53], and the red-shift has been attributed to the interaction of Mn to its environments in NC lattices as well as Mn-Mn coupling. It was also suggested that Mn-Mn coupling could cause some splitting energy levels between 4 T 1 and 6 A 1 states for the red-shift [53].…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…However, as shown in Figure 1, Mn doped in NCs do not present around 585 nm emission but a red-shift, and the PL shifts more towards the red region with the increase of Mn levels in Mn:AIZ/ZnS NCs. The red-shift by Mn doping was also observed in AIZS and other host NCs [53], and the red-shift has been attributed to the interaction of Mn to its environments in NC lattices as well as Mn-Mn coupling. It was also suggested that Mn-Mn coupling could cause some splitting energy levels between 4 T 1 and 6 A 1 states for the red-shift [53].…”
Section: Resultsmentioning
confidence: 82%
“…The red-shift by Mn doping was also observed in AIZS and other host NCs [53], and the red-shift has been attributed to the interaction of Mn to its environments in NC lattices as well as Mn-Mn coupling. It was also suggested that Mn-Mn coupling could cause some splitting energy levels between 4 T 1 and 6 A 1 states for the red-shift [53]. Because the Mn emission with Mn-Mn coupling could be a minor PL mechanism for the fast decay as we discussed, it is believed that the interaction of Mn to host NC lattices could be the major reason for the red-shift instead of Mn-Mn coupling.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…[(L)MnHal 3 ] and L 6 [Mn 3 Cl 12 ] type (L = protonated or alkylated N-base) [16][17][18][19][20][21][22] and Mn 2+ -doped sulfide and oxide nanocrystals [1,23,24] exhibit red emission. The compounds containing both tetrahedral and octahedral Mn II centers, e.g.…”
Section: Introductionmentioning
confidence: 99%